Potential prey traces of the javan leopard in Bromo Tengger Semeru National Park - Rheznandya Donny Minarto; Iska Desmawati; Agung Siswoyo; Bagaskara Raditya Wigita Putra (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2025)
The Javan leopard (Panthera pardus melas) is a subspecies of Panthera pardus endemic to Java Island, with a limited distribution on Java, Kangean, Nusakambangan, and Sempu Islands. It is the last remaining large carnivore on the island following the extinction of Panthera tigris sondaica. The species has been protected by the Indonesian government since 1970 under Decree No. 421/Kpts/Um/8/1970 and subsequent regulations, with continued protection through Government Regulation No. 7/1999, Law No. 5/1990, and Ministry of Environment and Forestry Regulation No. 106/MENLHK/SETJEN/KUM.1/12/2018. It is listed as Endangered on the IUCN Red List and in Appendix I of CITES. The population of P. p. melas continues to decline due to habitat degradation, reduced prey availability, and poaching. Bromo Tengger Semeru National Park (TNBTS) serves as a critical habitat for its survival. This study aims to document potential prey traces of P. p. melas in TNBTS. Field methods included direct observation of tracks and analysis of traces such as feces, skin derivatives (hair, scales, spines), footprints, feeding marks, nests, and wallows. The results identified Sus scrofa (40.9%) as the most frequent potential prey species, followed by Muntiacus muntjak (24.2%), Macaca fascicularis (10.6%), Hystrix javanica (9.1%), and both Viverricula malaccensis and Manis javanica (7.6% each). These findings highlight the essential role of prey availability in supporting P. p. melas populations in TNBTS. This information is expected to provide a basis for prey-based ecological conservation strategies and sustainable habitat management for the long-term survival of this keystone species.